Konflik Regulasi dan Masalah Kelayakan pada Kebijakan Izin Usaha Pertambangan bagi Ormas Keagamaan - Astinda, Afifudin Nur Rosyid; Pratama, Wahyu Pujo; Haidar, Muhammad Bagas (Universitas Semarang, 2024)
This study aims to examine the regulatory conflict regarding the granting of Mining Business Permits (IUP) to religious organizations and to assess whether, from a business law perspective, religious organizations are eligible to manage mining operations. This research employs a normative legal research method based on statutory regulations, specifically Law Number 3 of 2020 and Government Regulation (PP) Number 25 of 2024. The study also adopts a literature review approach, where the researcher examines literature discussing mining permits through research findings, reports, scientific studies, and other regulations related to the cases analyzed in this study, utilizing the business law perspective applicable in Indonesia. The study concludes that granting Mining Business Permits (IUP) to religious organizations is still not compliant with regulatory provisions. Furthermore, the eligibility of religious organizations to manage mining operations needs to be thoroughly assessed, particularly in terms of administrative compliance, financial capability, waste or environmental management, and technical requirements as stipulated in Law Number 3 of 2020 concerning Mineral and Coal Mining. Penelitian ini bertujuan untuk mengkaji konflik regulasi pemberian Izin Usaha Pertambangan (IUP) bagi Ormas keagamaan dan mengkaji apakah Ormas keagamaan dalam perspektif hukum bisnis layak untuk mengelola usaha pertembangan. Penelitian ini menggunakan metode penelitian hukum normatif yang didasarkan pada peraturan perundang-undangan Undang-Undang Nomor 3 Tahun 2020 dan Peraturan Pemerintah (PP) Nomor 25 Tahun 2024. Penelitian yang dilakukan juga menggunakan pendekatan studi literatur di mana peneliti mengkaji literatur yang membahas tentang izin pertambangan melalu hasil penelitian, laporan, kajian ilmiah dan peraturan lain yang berkaitan dengan kasus yang dikaji di dalam penelitian ini dengan menggunakan perspektif hukum bisnis yang berlaku di Indonesia. Penelitian ini menyimpulkan bahwa Izin Usaha Pertambangan (IUP) untuk Ormas keagamaan secara regulasi masih tidak sesuai dan kelayakan Ormas keagamaan dalam mengelola pertambangan masih perlu diuji baik secara administratif, kemampuan finansial, pengolahan limbah atau lingkungan, dan syarat-syarat teknis yang diatur dalam Undang-Undang Nomor 3 Tahun 2020 tentang Pertambangan Mineral dan Batubara.